RANCANG BANGUN SISTEM PERPUSTAKAAN DIGITAL (STUDI KASUS : SMK 1 BANDAR LAMPUNG) - Firnando Siyasih (Universitas Teknokrat Indonesia, 2021)
State Vocational High School 1 Bandar Lampung several activities have used computers, but especially in the processing of library data is still done manually, every month officers have to look at the book data and calculate the number of borrowers per day to make monthly reports, it is very retang against data damage, the problem caused is when going to make monthly report officers often have difficulty if there are documents that are damaged or lost. because the officer does not have a backup of the daily report data archive. Based on these problems, the system is designed to be able to develop and implement digital libraries that can be accessed through the website so as to improve the quality of library services without limited space and time. The digital library is expected to facilitate students in the process related to the library. Because the library will be created utilizing Web-based technology. With the user's website will be easier in finding a collection of books, scientific journals, and others needed by each member of the library. In addition, the website can also be accessed anywhere, anytime, and anyone without having to come to the location of smk negeri 1 Bandar Lampung library